A Rare Subcutaneous Manifestation of Metastatic Renal Cell Carcinoma - Darren Yak Leong Chan; Wei Jin Chua (Case Reports in Surgery)
We report a rare case of advanced metastatic renal cell carcinoma which initially presented to the clinic with back and forehead lumps. Ultrasound imaging of the lumps and later of the abdomen picked up a right renal tumour which led to further computed tomography and bone scans. The bone scan confirmed that the forehead lump was a calvarial metastasis and such a presentation for metastatic RCC is very rare which bears a significantly poorer prognosis.